Comparative analysis of the trends in the development of the northern cities of the world and Russia - Gavrilyeva, Tuyara (Louvain-la-Neuve: European Regional Science Association (ERSA), 2015)
It is known that cities are the engines of growth of the modern economy and society. Herewith we highlight the national and regional characteristics of urbanization as a global process. Somewhere the urbanization is stimulated, in China for example, somewhere it is limited, as we see in Russia. But it is a long-term trend, which will qualitatively change the life of humanity in the 21st century. There is a special interest in the comparative analysis of models of development in the northern cities of the world and Russia. They all have growth restrictions, such as the environment, the demographic capacity of the area, the high level of technological hazards. Thus, many have similar conditions: - Located near the water (sea and river), respectively, these are ports; - There is a highly developed transport infrastructure, including bridges; - The population is small; - Most are the educational and research centers; - Most are the administrative centres of the province (region), metropolises. In contrast to the sustainable state of the northern cities in Europe and America, where the dynamics of the main indicators remain stable for a long time, the state of the cities in the Russian North is differentiated. Yakutsk is the biggest city in terms of population, located in the permafrost zone. Now it is one of the fastest growing cities in the world. Over the past 15 years, the population of the city increased by 50%, from 195.4 thousand people in 2000 to 294.2 thousand people in 2014. In contrast, the other cities of the North of Russia (Norilsk, Vorkuta and Magadan) show population decline, deterioration of the economic situation. Fast growth, as well as a rapid decline, entail an increase in social risks. In addition, growth is also accompanied by an increase in technological and environmental risks. Currently, the most pressing issues for Yakutsk are: - Lack of social, communal and engineering infrastructure, poor quality of the land improvement. - Poverty of the population due to the weak labor market. - Growth ...